2007
DOI: 10.1007/s00428-007-0524-2
|View full text |Cite
|
Sign up to set email alerts
|

C-kit protein expression correlated with activating mutations in KIT gene in oral mucosal melanoma

Abstract: C-kit is a trans-membrane receptor tyrosine kinase (RTK) encoded by the proto-oncogene KIT located at 4q11-12. Gain-of-function mutations arising to c-kit activation independent of its ligand were observed in various tumors related to germ cells, mast cells, and interstitial cells of Cajal. C-kit also participates in melanocyte development; hence, its involvement in oral mucosal melanoma (OMM) tumorigenesis was investigated. Immunohistochemistry and mutation analysis were performed using 18 cases of human prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
120
2
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(138 citation statements)
references
References 39 publications
(59 reference statements)
11
120
2
5
Order By: Relevance
“…Our results regarding the limited utility of CD117 staining in ocular melanoma are in accordance with the majority of data from other melanoma subtypes. Studies of acral, mucosal, and cutaneous melanomas by Beadling et al, 8 Curtin et al, 9 and Rivera et al 28 have all shown limited correlation between CD117 staining intensity and KIT mutational status. Although Torres-Cabala et al 15 recently demonstrated a significant correlation between KIT mutational status and the percentage of CD117-positive tumor cells, irrespective of staining intensity, in their large series of acral, lentiginous, and mucosal melanomas, their positive predictive value was still low (14%).…”
Section: Discussionmentioning
confidence: 98%
“…Our results regarding the limited utility of CD117 staining in ocular melanoma are in accordance with the majority of data from other melanoma subtypes. Studies of acral, mucosal, and cutaneous melanomas by Beadling et al, 8 Curtin et al, 9 and Rivera et al 28 have all shown limited correlation between CD117 staining intensity and KIT mutational status. Although Torres-Cabala et al 15 recently demonstrated a significant correlation between KIT mutational status and the percentage of CD117-positive tumor cells, irrespective of staining intensity, in their large series of acral, lentiginous, and mucosal melanomas, their positive predictive value was still low (14%).…”
Section: Discussionmentioning
confidence: 98%
“…The MAPK pathway together with the phosphoinositide 3-kinase cascade (PI3K) can be triggered by activation of c-kit leading to the recruitment of signaling proteins involved in tremendous cell proliferation and survival (12). Mutations in c-kit have been identified in mucosal melanomas rendering c-kit as a promising molecular target (13)(14)(15).NRAS and BRAF mutations have been reported in subsets of mucosal melanomas, but most reports focused on combined mucosal sites (9,(16)(17)(18)(19). Most reports have claimed that NRAS and BRAF mutations are infrequent, justifying that mucosal melanoma is distinct from its cutaneous counterpart.…”
mentioning
confidence: 99%
“…MITF expression has been found in 40 to 91% of mucosal melanomas of the head and neck (Morris et al, 2008;Prasad et al, 2001). High rates of c-kit protein expression has been reported for mucosal melanomas and this immunohistochemical expression is associated with c-kit mutation (Rivera et al, 2008). A review of the literature report that 14% of mucosal melanomas harbor activating C-KIT mutations; 5% showed BRAF mutation and 14% oncogenic mutations in NRAS, which is much lower than the reported BRAF prevalence (56 to 59%) in cutaneous melanomas (Tacastacas et al, 2014;Cohen et al, 2004).…”
Section: Geneticsmentioning
confidence: 93%
“…Unlike cutaneous melanoma, BRAF mutation are infrequent and KIT mutation seem to be frequently altered (Lopez et al, in press;Soma et al, 2014;Kerr et al 2012;Buery et al, 2011;Junkins-Hopkins, 2010). (Tacastacas et al, 2014;Rivera et al, 2008).…”
Section: Genes Involved and Proteinsmentioning
confidence: 99%